Public-private partnership: opportunities for Ukraine - O. Sakal; H. Shtohryn; M. Ilina; Y. Shpylova; N. Tretiak; I. Denisenko; H. Byrkiv (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ)
The urgent necessity to reform the state sector of economy, to recover infrastructural objects, to attract foreign investments to Ukrainian economy, and to establish socially focused economy substantiates the great importance of development of the partnership relations between the public and private individuals (public-private partnership). Efficiency of such relations mainly depends on efficiency of legal regulation and development of organizational-economic structure. According to the law of Ukraine “About state-private partnership”, which principally regulates that kind of cooperation, the appropriate mechanism expects cooperation between the public, territorial (state partners) and legal (except for the state and communal enterprises) or private individuals, i.e. entrepreneurs (private partners). Focus of the mechanism on cooperation with territorial communities actualizes it because of a fast move of the power decentralization reform in Ukraine. At the level of a separate territorial community, practical application of any form of PPP requires from the representatives of local power to master legal, economic, social-communicative skills for initiation of the partnership (introduction of proposals and analysis of efficiency of the proposed projects), choice of private partners (one or several) and making agreements with them. Within such partnership, bodies of the state power or local self-government transfer a share of their authorities to a private partner (single or a group of them). Thus, private partnership (an individual or an enterprise) is responsible for implementation of the project, which aims at solution of some social-economic or ecological problems of the territorial community.